ASSTIVE DEVICE FOR PEOPLE WITH VISUAL IMPAIRMENT - Mrs. Anitha J,; Mr. Dhananjaya A, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Since time immemorial, society has struggled with the question of how best to aid persons who are blind or have some other form of visual impairment. Nevertheless, the development of a computer-aided tool is a sector that is still in the process of expanding its capabilities. All of these systems have been developed with the goal of providing the user with support in navigating without the need for the assistance of a second person. Various works make use of a variety of different computer vision methods. Nevertheless, there is no solution that can aid blind individuals with all of their core needs at this time and it is not currently accessible. Every one of the systems that are currently operational was designed specifically to do one particular task. For the purpose of this project, we suggest a novel approach to giving aid to visually impaired individuals that brings together the most important aspects of a variety of successful approaches as well as some extra functionalities. It's feasible that this brand-new approach may help blind individuals overcome some of the most major obstacles they still confront. In addition to this, we give a comparison and analysis of the many different approaches that are presently being utilised for complete navigation.